Exploring everyday experiences of cultural diversity: The construction, validation, and application of the normative multiculturalism scale. (19th October 2018) - Stuart, Jaimee; Ward, Colleen
Abstract: The 3‐factor structure of the Normative Multiculturalism Scale (NMS)—Contact with Diversity (CD), Multicultural Ideology (MI), and Multicultural Policies and Practices (MPP)—was tested and confirmed with community samples from New Zealand ( N  =   381) and the United States ( N  =   311). Correlations with criterion measures (e.g., perceived minority disadvantage and attitudes to diversity) supported the criterion validity of the subscales. NMS factors were then examined as predictors of social connectedness in a British community sample ( N  =   347). Hierarchical multiple regression revealed that MI predicted general trust, and MI and MPP predicted national attachment. While MPP was associated with greater perceived threat, this relationship was dampened by the joint influences of MI and CD. The research presents a novel perspective on multiculturalism by adopting a normative approach and examining the main and interaction effects of contact with diversity, multicultural ideology, and multicultural policies on interpersonal and intergroup outcomes.